Reducing Distortions in International Commodity Markets : An Agenda for Multilateral Cooperation - Hoekman, Bernard (2012)
Global commodity markets are affected by a variety of government policies that may expand or lower overall supply and as a result affect world prices for the specific products concerned. Market failures and market structures (market power along the value chain) also affect supply. This paper briefly reviews a number of factors that may distort international commodity markets with a view to identifying elements of an agenda for multilateral cooperation to reduce such distortions. Much of the policy agenda that arises is domestic and requires action by national governments. But numerous policies -- or absence of policy -- generate international spillovers that call for the negotiation of international policy disciplines. Independent of whether distortions are local or international in scope, the complexity of prevailing market structures and their impacts on efficiency call for much greater monitoring and analysis by the international community.